The Moderation of Islamic Lecturing in Da’wa Movements: A Case Study of Maos Community in Cilacap, Central Java - Mujamil, Ashari; Fatimah, Siti (An-Nida', 2023)
The role of Islamic movements (ormas) as da’wa institutions contributes significantly to efforts to build a civil society. As observed in Maos Lor Village, Cilacap, Central Java, there are five types of Islamic movements conducting da’wa activities side by side, including Nahdlatul Ulama (NU), Muhammadiyah, Lembaga Dakwah Islam Indonesia (LDII), Jamaah Muslimin (Hizbullah), and Salafi. The aim of this research is to understand and analyze the socio-historical dialectics institutionally among these Islamic movements, the types of da’wa activities, and their impact on the social construction of society in creating religious moderation. This paper is a qualitative study employing field research with social construction theory as the analytical tool, particularly focusing on three stages of social construction: externalization, objectivation, and internalization. The findings reveal that in the stages of externalization and objectivation, each organization experiences periodic dynamics in its history, characterized by ideological and attitudinal friction. This is marked by the initial construction dynamics where only two Islamic movements, NU and Muhammadiyah, with traditionalist and modernist ideologies, were present. Subsequent turmoil occurred with the emergence of other Islamic movements from the 1970s to the 1990s, namely the Jamaah Muslimin (Hizbullah), LDII, and Salafi groups. Until the 2000s, there were religious attitude frictions such as mosque disputes, and congregation shifts from one organization to another. However, once a moderate stance emerged, marked by the internalization stage involving da’wa activities of each organization along with openness and tolerance, it demonstrated that even in small rural communities, religious moderation could be experienced and exemplified in nation-building efforts. Abstrak: Peran organisasi masyarakat (ormas) Islam sebagai lembaga dakwah dalam upaya membangun masyarakat madani memiliki sumbangsih yang penting. Sebagaimana yang terdapat di Desa Maos Lor, Cilacap, Jawa Tengah terdapat lima  macam organisasi masa (ormas) Islam yang melakukan aktivitas dakwah secara berdampingan, diantaranya yaitu, Nahdlatul Ulama (NU), Muhammadiyah, Lembaga Dakwah Islam Indonesia (LDII), Jamaah Muslimin (Hizbullah), dan Salafi. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis dialektika sosio-historis secara institusional ormas Islam tersebut, jenis kegiatan dakwah, serta dampaknya terhadap konstruksi sosial masyarakat dalam menciptakan moderasi beragama. Tulisan ini merupakan penelitian kualitatif berjenis studi lapangan dengan teori konstruksi sosial sebagai alat analisis, khususnya tigatahapan dialektika konstruksi sosial yaitu eksternalisasi, objektivikasi dan internalisasi. Hasilnya, dalam tahap eksternalisasi dan objektivikasi, masing-masing ormas memiliki dinamika secara periodik dalam sejarahnya berupa gesekan ideologi dan sikap. Hal ini ditandai dengan dinamika yang terjadi pada konstruksi awal yang hanya terdapat dua ormas Islam NU dan Muhammadiyah dengan ideologi tradisionalis dan modernis. Gejolak selanjutnya terjadi seiring munculnya ormas Islam lain mulai tahun 1970-an sampai tahun 1990-an, yaitu kelompok Jamaah Muslimin (Hizbulah), LDII, dan Salafi. Hingga tahun 2000-an, terjadi gesekan sikap dalam beragama seperti perebutan masjid sampai dengan perpindahan jemaah dari satu ormas ke yang lainnya. Namun, saat sudah muncul sikap moderat yang ditandai dengan tahap internalisasi berupa aktivitas dakwah masing-masing ormas serta keterbukaan dan toleransi. Hal ini membuktikan bahwa dalam ranah masyarakat kecil di pedesaan sekalipun, moderasi beragama dapat dirasakan sekaligus dijadikan percontohan dalam berbangsa dan bernegara.